Efektifitas pemberian dosis pupuk kotoran ternak ayam terhadap produksi rumput Brachiaria humidicola pada pemotongan pertama dan kedua - Maria Erviana Kusuma (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2016)
The aim of this research were to know the effect of dosage of chicken manure and to determine the dosage of chicken manure that giving the best result to the production of Brachiaria humidicola at the first and second defoliation. This research was designed by using Completely Random Design (CRD) with single factor experiment that is dosage of chicken manure (A), that is a0 = without chicken manure (control), a1 = 20 ton ha-1, a2 = 30 ton ha-1 and a3 = 40 ton ha-1. The result showed that the applications of chicken manure dosage give effect on the number of chicks, the crop height and the production of Brachiaria humidicola at the first and second defoliation. The applications of chicken manure on doses 20 ton ha-1, 30 ton ha-1 and 40 ton ha-1 give same effect on the production of Brachiaria humidicola. The effectiveness of applications showed degradation of production at the second defoliation compared with first defoliation. Key words : Brachiaria humidicola, chicken manure, second defoliation, production